Vaptans or voluntary increased hydration to protect the kidney: how do they compare?. Issue 3 (29th September 2021) - Bankir, Lise; Guerrot, Dominique; Bichet, Daniel G
ABSTRACT: The adverse effects of vasopressin (AVP) in diverse forms of chronic kidney disease have been well described. They depend on the antidiuretic action of AVP mediated by V2 receptors (V2R). Tolvaptan, a selective V2R antagonist, is now largely used for the treatment of patients with autosomal dominant polycystic kidney disease. Another way to reduce the adverse effects of AVP is to reduce endogenous AVP secretion by a voluntary increase in fluid intake. These two approaches differ in several ways, including the level of thirst and AVP. With voluntary increased drinking, plasma osmolality will decline and so will AVP secretion. Thus, not only will V2R-mediated effects be reduced, but also those mediated by V1a and V1b receptors (V1aR and V1bR). In contrast, selective V2R antagonism will induce a loss of fluid that will stimulate AVP secretion and thus increase AVP's influence on V1a and V1b receptors. V1aR is expressed in the luminal side of the collecting duct (CD) and in inner medullary interstitial cells, and their activation induces the production of prostaglandins, mostly prostaglandin E2 (PGE2). Intrarenal PGE2 has been shown to reduce sodium and water reabsorption in the CD and increase blood flow in the renal medulla, both effects contributing to increase sodium and water excretion and reduce urine-concentrating activity. Conversely, non-steroidal anti-inflammatory drugs have been shown to induce significant water and sodium retention and potentiate the antidiuretic effects of AVP. Thus, during V2R antagonism, V1aR-mediated actions may be responsible for part of the diuresis observed with this drug. These V1aR-dependent effects do not take place with a voluntary increase in fluid intake. In summary, while both strategies may have beneficial effects, the information reviewed here leads us to assume that pharmacological V2R antagonism, with resulting stimulation of V1aR and increased PGE2 production, may provide greater benefit than voluntary high water intake. The influence of tolvaptan on the PGE2 excretion rate and the possibility to use somewhat lower tolvaptan doses than presently prescribed remain to be evaluated.